Cover Feature: A Pyrene‐Modified Serinol Nucleic Acid Nanostructure Converts the Chirality of Threoninol Nucleic Acids into Circularly Polarized Luminescence Signals (Chem. Eur. J. 59/2021). Issue 59 (8th October 2021) - Kashida, Hiromu; Nishikawa, Keiji; Ito, Yuka; Murayama, Keiji; Hayashi, Ichiyo; Kakuta, Takahiro; Ogoshi, Tomoki; Asanuma, Hiroyuki
Abstract : Creating chiroptical signals : A circularly polarized luminescent (CPL) probe composed of serinol nucleic acids forms a one‐dimensional nanostructure and expresses no CPL signals. However, helicity is induced when a chiral nucleic acid is added. As a result, the probe can switch CPL signals depending on the chirality of added nucleic acids. These findings will provide a new platform to convert the chiral information of biomolecules into chiroptical signals. More information can be found in the Communication by H. Kashida, H. Asanuma et al. (DOI: 10.1002/chem.202102333 ).